Penerapan Algoritma Levenstein Distance Untuk Pencarian Judul Pada Aplikasi Lagu-Lagu Nasional - Hyasinta Oktavia Nahampun (STMIK Budi Darma, 2023)
The Levenshtein Distance algorithm is a deletion, insertion and swap operation. Based on the test results that have been carried out, the levenshtein Distance algorithm is able to calculate the edit distance obtained from the matrix used to calculate the number of strings differences between two strings. The calculation of the distance between these two stings is determined from the minimum number of change operations to make string A into sting B. There are 3 main types of operations that can be performed by this algorithm: 1. change characters 2. add characters 3. delete characters This algorithm runs from the corner. top left of a two-dimensional array that has been filled with a number of characters from the initial string and the sting target and given the cost value. The cost value in the lower right corner becomes the edit distance value which represents the difference between the two strings.